2013
DOI: 10.1007/s00247-013-2751-9
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion cysts in the paediatric wrist: magnetic resonance imaging findings

Abstract: Ganglion cysts were frequently found in children referred for wrist MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Earp noted a gender distribution of 3:1 (female:male) in kids with chronic wrist pain caused primarily by scapholunate tears, 10 and Bracken described a female predominance of 2:1 when evaluating ganglion cysts in children. 5 Similarly, Farr reported a distribution of 4.6:1 for their series of children/adolescents advanced to wrist arthroscopy for therapy-refractory pain, although they also note that their results were likely affected by a higher incidence of girls with upper extremity malformation. 12 Beyond the baseline differences at initial presentation, our results also showed that the female predominance increased even further to 2.4:1 when quantifying the frequency of a normal MRI in those presenting with wrist pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earp noted a gender distribution of 3:1 (female:male) in kids with chronic wrist pain caused primarily by scapholunate tears, 10 and Bracken described a female predominance of 2:1 when evaluating ganglion cysts in children. 5 Similarly, Farr reported a distribution of 4.6:1 for their series of children/adolescents advanced to wrist arthroscopy for therapy-refractory pain, although they also note that their results were likely affected by a higher incidence of girls with upper extremity malformation. 12 Beyond the baseline differences at initial presentation, our results also showed that the female predominance increased even further to 2.4:1 when quantifying the frequency of a normal MRI in those presenting with wrist pain.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at specific injuries, MRI is the imaging modality of choice for radiographically occult scaphoid fractures, which represented 33% of all indications in this study. 3,18,21,24 In children, MRI is also useful in the workup of a variety of other radiographically occult findings, including ganglion cysts, 5 Madelung’s deformity, 15 and physeal injuries, among others. 11 Here, in a pediatric-only cohort, 73% of all wrists had at least 1 abnormal finding.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with recurrent DWG cysts, especially those after open surgery, thick scarring commonly occurs between the scapholunate ligament and capsule on the dorsal wrist, 5,14 which might result in a recurrent cyst with a multilocular feature. Previous studies have demonstrated that a multiloculated ganglion cyst can be clearly identified on MRI scans 22 . In this study, a comprehensive evaluation based on preoperative wrist MRI scans was performed, including the unilocular or multilocular characteristics of the cyst as well as the limits between the ganglion wall and extensor tendons, to direct capsulectomy and cyst excision under arthroscopic view.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that a multiloculated ganglion cyst can be clearly identified on MRI scans. 22 In this study, a comprehensive evaluation based on preoperative wrist MRI scans was performed, including the unilocular or multilocular characteristics of the cyst as well as the limits between the ganglion wall and extensor tendons, to direct capsulectomy and cyst excision under arthroscopic view. This could be another reason for the low recurrence rate observed in this study.…”
Section: Discussionmentioning
confidence: 99%